APLIKASI ANDROID MENGGUNAKAN LOCATION BASED SERVICE (LBS) UNTUK NAVIGASI TUJUAN WISATA DI KABUPATEN GARUT - Asep Nanang Sutisna; Cecep Taofik; Ali Mulyawan (STMIK Mardira Indonesia, Bandung, 2020)
Garut Regency is a Regency in West Java Province, Indonesia. The capital is Tarogong Kidul. The regency is adjacent to Sumedang regency in the north, Tasikmalaya regency in the east, Indian Ocean in the south, and Cianjur and Bandung regencies. The number of tourists who travel in Garut regency, making the workers in the tourism office burdened with the many questions surrounding the location thrown by local and foreign tourists. With Location Based Service technology, tourists can find the location of the desired tourist position without a guide from the tour guide though. In this study the authors use research methods Develoment Life Curcle Software (SDLC) waterfall (Waterfall), while for application method using Location Based Service (LBS). This application utilizes Global Positioning System (GPS) that has been integrated with the handset. With the LBS application is expected to provide accurate information, clear and precise to know the points of location Nature Tourism Garup Kabupatem, and can facilitate local and foreign tourists and the community, especially Garut regency. Keywords: Garut, Location Based Service, Software Development Life Cycle, Waterfall, TourDOI : http://doi.org/10.5281/zenodo.3929065